Genetic Characterization of Wheat (Triticum aestivum L.) Germplasm for Moisture Stress Tolerance Using in-vivo and in-vitro Techniques: Genetic characterization of wheat for moisture stress tolerance - Sharma, Komal; Rana, Vijay; Kumar, Nimit (Journal of Cereal Research, 2025)
ABSTRACT The present investigation entitled “Genetic characterization of wheat (Triticum aestivum L.) germplasm for moisture stress tolerance using in vivo and in vitro techniques” was carried out during rabi, 2023-24 at the Rice and Wheat Research Centre, Malan. The experiments were laid out in α lattice design with three replications under both rainfed (E1) and irrigated (E2) and experimental lines were also evaluated at different levels of osmotic stress by using PEG-6000 (C1: control; C2: -3 bar; C3: -6 bar: C4: -9 bar) under controlled condition. The experimental material comprised 40 wheat genotypes including five checks. The data were recorded for various agro-morphological traits viz., days to 50 % flowering, days to 75% maturity, peduncle length, plant height, biological yield/plant, grain yield/plant, harvest index and 1000-grain weight. In lab conditions, data were recorded for various germination and seedling traits viz., germination percentage, root length, shoot length, root-shoot ratio, coleoptile length and seedling vigour index under different osmotic stress levels. Analysis of variance revealed that mean squares due to genotypes were significant for all the characters under both field and controlled conditions indicating the presence of adequate amount of variability among wheat genotypes. For different traits, high heritability coupled with moderate to high genetic advance was observed for plant height, peduncle length, biological yield/plant, grain yield/plant, 1000-grain weight and harvest index indicating their importance in the improvement of grain yield. Grain yield/plant was found to be positive and significantly associated with biological yield/plant, harvest index and 1000-grain weight under both the environments. Under controlled conditions, high heritability coupled with high genetic advance was recorded for shoot length, coleoptile length and seedling vigour index at different osmotic stress levels. The seedling and germination traits showed significant and positive correlation among themselves The seedling traits viz., germination percentage and seedling vigour index (for all stress levels) showed positive correlation with grain yield/plant. Based on the drought susceptibility index, HPW 368 was found to be the most drought-tolerant genotype, because it exhibited the lowest DSI value (-1.67) followed by HPW 493 (-1.56), VL 2053 (-0.76), RIL 45 (-0.56), VL 2041 (-0.51), TYRM 2 (-0.31), PBW 752 (-0.21, PBW 725 (-0.10), PBW 872 (0.14), DBW 187 (0.18) and so on. PW 2201, HPW 490, Sharbati, HPW 489, HPW 491, SKW 368 and SKUAW 102 were identified as better-performing genotypes for in vivo and in vitro traits. Based on lower drought susceptibility index values, these genotypes were categorized as drought tolerant. The positive rank correlation between the various in vivo (rainfed) and in vitro stress (-6 bar) conditions indicated that the performance of a genotype under field conditions was similar to its performance under laboratory conditions. Hence, the selection for a crucial and complex trait like drought tolerance in wheat can be enhanced in vitro by including selection criteria along with evaluation under field conditions.